2008
DOI: 10.1038/jhh.2008.10
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and cardiac arrhythmias: a review of the epidemiology, pathophysiology and clinical implications

Abstract: Hypertension is commonly associated with cardiac arrhythmias in patients with and without concomitant cardiovascular disease. Experimental and epidemiological studies have demonstrated potential links between hypertension and atrial and ventricular arrhythmias, although the underlying pathophysiological mechanism remains unclear. Nonetheless, the importance of hypertension as a cause of atrial and ventricular arrhythmias is not well recognized. In particular, the occurrence of left ventricular hypertrophy is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 93 publications
2
19
0
4
Order By: Relevance
“…A large number of clinical and epidemiologic studies [1,2] have reported a correlation between the mass increase of the left ventricle (LV) and the risk of disease or death. The prevalence of left ventricular hypertrophy (LVH) in patients with essential hypertension may be as high as 40% (12-70%) [3].…”
mentioning
confidence: 99%
“…A large number of clinical and epidemiologic studies [1,2] have reported a correlation between the mass increase of the left ventricle (LV) and the risk of disease or death. The prevalence of left ventricular hypertrophy (LVH) in patients with essential hypertension may be as high as 40% (12-70%) [3].…”
mentioning
confidence: 99%
“…There are studies which show the possible links between hypertension and atrial and ventricular arrhythmias, though the principal pathophysiological mechanism remains unclear (Yiu and Tse, 2008). The prevalence and risk factors for arrhythmias vary among men and women (Wolbrette et al, 2002).…”
Section: Arrhythmiamentioning
confidence: 99%
“…A large number of clinical and epidemiological studies [1,2] have reported a correlation between the mass increase of the left ventricle (LV) and the risk of disease or death. The prevalence of left ventricular hypertrophy (LVH) in patients with essential hypertension may be as high as 40% (12%-70%) [3].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%